SISTEM MANAJEMEN PAGUYUBAN REYOG PONOROGO JABODETABEK - Nursilah; Ida Bagus Ketut Sudiasa; Novitasari, Syifa (Program Studi Pendidikan Tari FBS UNJ, 2023)
This study aims to describe the management system of the Reyog Ponorogo Association in Jabodetabek. The Reyog Ponorogo Association is an organization that still exists and preserves the Reyog Ponorogo in Jabodetabek. This research is a qualitative descriptive study. The subject of this research is the Reyog Ponorogo Association in Jabodetabek. The research is focused on the study of association management exposure. Data were obtained by direct observation techniques, in- depth interviews, and documentation studies. Data were analyzed using qualitative descriptive analysis techniques. The validity of the data is obtained through triangulation through the source stage, namely checking data from various sources. These sources are the results of observations, interviews, and documentation about the Reyog Ponorogo Association in Jabodetabek. This research obtained the following results; (1) The planning process in the form of making 3-month work programs and annual work programs, logos, and ADART of the Reyog Ponorogo Jabodetabek Association (2) Organizing/implementation systems that are carried out by creating organizational parts/structures with respective fields determined by the leadership, (3) The process of directing in terms of the implementation of activities that have been planned so that it goes well, (4) Control that functions to guarantee and ensure the achievement of targets set in the planning process.